O aksjomatyzacji ekonomii - uwagi na półwiecze nowoczesnej teorii równowagi - Malawski, Andrzej (Axiomatization of Economics. Remarks in Connection with Half-Centenary of Modern Theory of Equilibrium, 2006)
Fifty years have passed since the time when a series of papers, that revolutionized the economic theory, was published. In the approach presented therein some parts of economic science have taken the form of axiomatic-deductive systems. In this framework the fundamental problems of the existence for general competitive equilibrium and its Pareto optimality have been solved. These achievements have defined the standards of scientific rationality, rigor, generality and simplicity of the analysis respected up to now in the economic research. In this context comments on the process of axiomatization of economic theory, its roots, limitations, empirical adequacy and mathematics as the language of today science are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 114-121